Impact of Demonetization on Small and Medium-Sized Businesses - Saidulukelothu; Dinesh Chandra (Journal of Biomedical and Pharmaceutical Research, 2023)
ResearchGate, SSRN, Google Scholar, and Academia were used to conduct a systematic literature review on digital payment systems used by bank customers. Key words included digital banking, internet banking, digital payment, customer adoption, perception, and conceptual framework. In order to conceptualize the research, we scanned and read all of the relevant literature. The adoption of a digital payment system was researched using ABCD analysis, which was also utilized to build a search proposal. The evaluation method uncovered both individual and societal elements that play a role in the rising popularity of digital payments among banking clients. Various research gaps were identified in the area of digital payment strategy adoption, and various suggestions were made to increase the rate at which consumers adopted digital payment methods. Systematic investigation has shown a distinct image of the digital system adoption by banking consumers. The research also found that there is a connection between customers and individual and demographic aspects, as well as between consumers and different strategies to improve use patterns. Increasing the number of consumers is one of the goals of Digital India, and its implementation will help the country get there. Systematic reviews are a kind of academic paper. Keywords: Cashless transactions, digital currency, and the Indian economy